The Influence of Financial Self-Efficacy and Peer Influence Regarding Investment Decisions on Financial Assets: Comparative Gen Z in Mataram and Surabaya with Risk Tolerance As a Moderating Variable - Afifah Putri Maharani; Burhanudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of financial self-efficacy and peer influence on Gen Z financial asset investment decisions in Mataram and Surabaya, with risk tolerance as a moderating variable, amidst low financial literacy (38%) and the dominance of young investors. The objective is to analyze causal relationships and cross-regional comparisons. Using a comparative explanatory quantitative approach with PLS-SEM, the Gen Z investor population (17-28 years old) was purposively snowball-sampled (260 respondents). The 5-point Likert questionnaire instrument was analyzed via SmartPLS (outer/inner model, MRA, PLS-MGA). The results show that financial self-efficacy has a significant effect (t=8.914, p=0.000), peer influence is weakly significant (t=1.896, p=0.029), but risk tolerance does not moderate (p>0.05); the model explains 66.9% of the variation. Conclusion: Strengthening self-efficacy for rational Gen Z decisions across regions.